Does Energy Infrastructure Reduce Inequality Inter-regional in Riau Province, Indonesia? - Hidayat, Muhammad; Darwin, Ranti; Hadi, M. Fikry (International Journal of Energy Economics and Policy, 2019)
This research aims to determine the effect of energy infrastructure on the dynamics of development inequality that occurs between regions in Riau Province by adding economic growth and balanced funds as control variables. The analysis used dynamic panel data modeling with Generalized Method of Moment (GMM) approach and datasets from 12 regions in 7 years starting from 2011 to 2017. The results of the model show that the inequality of the previous period and economic growth can significantly increase inequality. Whereas balance funds and electricity infrastructure have a negative and significant influence, or can reduce inequality significantly. These results provide evidence that energy infrastructure can reduce inequality. Keywords: Inequality, Energy Infrastructure, GMM, Riau JEL Classifications: C33, D63, Q43 DOI: https://doi.org/10.32479/ijeep.8658